The Relation of the Vascular Flora to some Factors of site in the Mesters Vig District, Northeast Greenland. - Raup, Hugh M. (Meddelelser om Grønland, 1969)
A method of analysis is presented for botanical data gathered in the Mesters Vig district, Kong Oscars Fjord, Northeast Greenland, in the summer seasons of 1956, '57, '58, '60, and '64. The work was done in collaboration with Dr. A. L. WASHBURN who was at the same time making detailed studies of geomorphic processes. The basic information used in the present paper was published in 1965 (RAUP, 1965 A), where it was dispersed throughout a floristic treatment of the Mesters Vig vegetation. Here it is collated in terms of the species' behavior with respect to their tolerance of variation on gradients of ground cover, moisture, and physical disturbance of the soils. Information on frequency and on the nature of roots and underground stem systems is also brought together. The flora is then analyzed in terms of the behavior of the species on the various gradients, using a 3-fold division in the rating of their tolerance to variation in the gradients. "Wide tolerance" indicates that a species was found growing successfully in 2/3's or more of the possible variations in a given gradient. "Narrow tolerance" means that a species was found in sites with only 1/3 of the possible variations or less. " Intermediate tolerance" indicates that a species was found in sites having between 1/3 and 2/3's of the possible variations. Lists of species for each of these tolerance categories are given for each of the gradients used. Data on coverage of the ground were obtained by estimating the percentage of the ground surface in a given site which was covered by living vascular plants when viewed from above. Moisture categories used were high, medium, and low. These were based upon ocular evaluations in the field and upon moisture analyses of soil collections. Two gradients were used in the analyses of the species' reactions to physical disturbance. The first was for disturbances induced by frost action, primarily frost heaving: the " frost disturbance gradient". The second, called the " nonfrost disturbance gradient", involved disturbances due to all other geomorphic processes that appeared to be limiting to the growth of plants. Most of the judgments made on the intensities of disturbances came from detailed studies being made concurrently by Dr. WASHBURN. Assuming that the success with which a species could become established and persist was closely related to its reactions to external factors of the habitat, the species included in the major frequency classes were analyzed in terms of percentages that fell into widely and narrowly tolerant groups on each of the gradients. Widely tolerant species made up the bulk of the vegetation (common to abundant species), while narrowly tolerant ones were mainly the rare to occasional species. The paper contains a general review of previous research that has been pertinent and useful to the Mesters Vig studies.